Asperization of dental cavity to maximize the adhesion of restorations in noncarious cervical lesions (NCCL) using a universal adhesive system in the conventional mode: double blind randomized clinical trial - Mattana, Rafaela Caroline (2019)
OBJECTIVE: This double-blind randomized clinical trial evaluates the influence of asperizarition on clinical behavior of Peak® Universal Bond adhesive system (Ultradent Products, USA) as etch-and-rinse (ER) in non- cariouscervical lesions (NCCLs). MATERIAL AND METHODS: A total of 92 restorations were randomly placed in 26 patients according to the following groups: Etch-and-rinse (ER) (no preparation) and etch-and-rinse and asperization (ERa). The resin composite Forma® Plus (Ultradent Products, USA) was placed incrementally. The restorations were evaluated at baseline, 6 and 12 months, using the FDI and USPHS criteria. Statistical analyses were performed using Friedman repeated-measures analysis and Mc Nemar's test (α=0.05). RESULTS: 13 restorations were lost at 12 months (6 for ER, 7 for ERa) (p >0.05 between groups). No restoration showed recurrent caries lesion at 12 months. 74 restorations were considered to have minor discrepancies in marginal adaptation at the 12 month recall using the FDI criteria (40 for ER, 44 for ERa p >0.05 between groups). CONCLUSION: The asperization before application of Peak® Universal Bond adhesive system as etch-and-rinse didn't affect the clinical behavior of composite restorations placed in NCCLs.